Faktor Determinan Kualitas Laba dengan Profitabilitas sebagai Variabel Moderasi - Anjani, Nadya Zalianti Puspa; Wahyuni, Sri; Setyadi, Edi Joko; Mudjiyanti, Rina (Owner : Riset dan Jurnal Akuntansi, 2024)
This study aims to measure the effect of liquidity, company size and accounting conservatism on earnings quality with profitability as a moderating variable. This research data was collected through secondary data sources obtained through the website www.idx.co.id or the official website. The population taken was 77 companies operating in the food and beverage sector. During the 4 year observation period, namely 2018 to 2021, the total sample used was 120 companies in this sector. In analyzing the data, this research used descriptive statistical test techniques, classical assumption tests, multiple linear regression (MRA), and hypothesis testing using the SPSS application. The results of hypothesis testing prove that liquidity has a significant positive effect on earnings quality, while company size, accounting conservatism, and profitability do not have a significant effect on earnings quality. In the moderation test, profitability cannot moderate the effect of liquidity, company size and accounting conservatism on earnings quality.